ETIKA KEPEMIMPINAN DALAM KONTEKS GLOBALISASI: ANALISIS TERHADAP KUALITAS DAN AKSES PENDIDIKAN - Rahayu Rahmadani; Ira maya sofa; Nova Arianti; Rahma Yuni; Ramayulis Rahman; Ratna Juita; Alfroki Martha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze how globalization affects leadership ethics and identify the educational issues that arise as a result of this phenomenon. The methodology used is a literature study and qualitative analysis of relevant data, including interviews with educational leaders and analysis of educational policies in various countries. The results show that leaders need to understand cultural complexities and apply ethical principles in decision-making. In addition, although globalization provides greater access to knowledge, the access gap and commercialization of education are significant challenges. The research recommends the development of digital infrastructure, curriculum revision and teacher training to improve the quality of education. In addition, international collaboration and strengthening local values in education are also considered important to maintain cultural identity amid globalization. The findings are expected to provide insights for leaders and policymakers in facing the challenges of globalization ethically and effectively